Efektivitas Pengelolaan Bantuan Langsung Tunai Dana Desa pada Masa Pandemi Covid-19 - Winanti, Ni Kadek Astri; Gayatri, Gayatri (E-Jurnal Akuntansi, 2023)
Karangasem Regency is one of 21 other regencies that has succeeded in disbursing Direct Cash Assistance from Village Funds reaching 59.7%. Manggis District is one of the sub-districts in Karangasem Regency that has disbursed Direct Village Fund Cash Assistance in 12 village areas. This research aims to examine the influence of accountability, transparency and community participation on the effectiveness of managing Village Fund Direct Cash Assistance. The sample used for this research was 119 village officials. Determining the sample in this research used a non-probability sampling method with a purposive sampling technique. Data was collected using a questionnaire method. The research results reveal that accountability, transparency and community participation have a positive effect on the effectiveness of managing Village Fund Direct Cash Assistance. Keywords: Accountability; Transparency; Community Participation.